Effect of chemical conversion induced by self-corrosion of zinc powders on enhancing corrosion protection performance of zinc-rich coatings. (January 2022) - Ma, Qian; Wang, Lida; Sun, Wen; Yang, Zhengqing; Wang, Suilin; Liu, Guichang
Abstract: Protection performance of zinc-rich coatings is generally ascribed to sacrificial anode protection and physical shielding derived from corrosion products, neglecting the contribution of zinc fillers' self-corrosion. This work clarifies the fact that self-corrosion of zinc powders can induce active protection behaviour of zinc-rich coatings by chemical conversion for corrosive media, firstly building "chemical shielding" function, and then enhancing physical shielding protection during the formation of zinc corrosion products. Chemical and physical shielding effects enhance shielding performance of zinc-rich coatings and extend its cathodic protection life. The result is beneficial to enrich protection theory of zinc-rich coatings. Highlights: Active protection of zinc-rich coatings is studied besides cathodic protection. Self-corrosion of zinc actively traps corrosive media by chemical conversion. Chemical conversion for oxygen dominates the "chemical shielding" function. Chemical shielding function is the premise of enhanced physical shielding effect. Chemical and physical shielding effects jointly endow active protection.